If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -7y + 5 = 2y + 11 + -7y Reorder the terms: 4 + 5 + -7y = 2y + 11 + -7y Combine like terms: 4 + 5 = 9 9 + -7y = 2y + 11 + -7y Reorder the terms: 9 + -7y = 11 + 2y + -7y Combine like terms: 2y + -7y = -5y 9 + -7y = 11 + -5y Solving 9 + -7y = 11 + -5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '5y' to each side of the equation. 9 + -7y + 5y = 11 + -5y + 5y Combine like terms: -7y + 5y = -2y 9 + -2y = 11 + -5y + 5y Combine like terms: -5y + 5y = 0 9 + -2y = 11 + 0 9 + -2y = 11 Add '-9' to each side of the equation. 9 + -9 + -2y = 11 + -9 Combine like terms: 9 + -9 = 0 0 + -2y = 11 + -9 -2y = 11 + -9 Combine like terms: 11 + -9 = 2 -2y = 2 Divide each side by '-2'. y = -1 Simplifying y = -1
| -3/4=x/3 | | x*y=240 | | x*y=250 | | a/9-15 | | -2a/3=-3/4 | | 4(x-5)-3(x-2)=1 | | c=180+65h | | (11-7)+g= | | 4-(4-4k)=-10-16 | | 35=w+7 | | 38=-11a-a^2 | | 3/4w=1/5 | | 15=7.5 | | 11v^2-15v+132=10v^2 | | 6(x+-1)=2+8x | | x/1.2=5 | | x+1/2-1=7 | | 3x-15/3=5 | | 48+9(y-7)= | | x/3.7=2.1 | | 3x-7+2x=13 | | 3x/2-3=3 | | 2n^2+12n+36=-7 | | m+(-4.4)=-3.6 | | (3+4x)(5+6x)= | | 4-6x=3x+11 | | 2.1*4.1= | | 0.5x^2+x+0.5=0 | | 3(x-5)+8=-(2-x)-25 | | -2.1x=14 | | p^2+6p-41=0 | | 3x+12=7(2x-3) |